2019
DOI: 10.1039/c9cy01791g
|View full text |Cite
|
Sign up to set email alerts
|

Highly improved acetone oxidation activity over mesoporous hollow nanospherical MnxCo3−xO4 solid solutions

Abstract: Mesoporous hollow nanospherical MnxCo3−xO4 solid solutions synthesized by a facile solvothermal alcoholysis have been developed to catalyze acetone oxidation for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 61 publications
1
38
0
Order By: Relevance
“…1d), which is similar with the particle size in the Au/ In addition, two XPS sets were found at 795.1 and 780.0 eV with an energy difference of $15.1 eV, which corresponds to Co 2p 1/2 and Co 2p 3/2 spin-orbit-split doublet peak of Co 3 O 4 spinel. [33][34][35][36][37] The Co 2p 3/2 peak of 780.0 eV is tted and deconvoluted into two peaks of 780.8 and 779.2 eV (Fig. 2b and e), which is attributed to Co 2+ and Co 3+ species, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…1d), which is similar with the particle size in the Au/ In addition, two XPS sets were found at 795.1 and 780.0 eV with an energy difference of $15.1 eV, which corresponds to Co 2p 1/2 and Co 2p 3/2 spin-orbit-split doublet peak of Co 3 O 4 spinel. [33][34][35][36][37] The Co 2p 3/2 peak of 780.0 eV is tted and deconvoluted into two peaks of 780.8 and 779.2 eV (Fig. 2b and e), which is attributed to Co 2+ and Co 3+ species, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…These signals correspond to the presence of unpaired electrons at sites of low atomic densities (as shown on HAADF images), which are resulted from the Zeeman effect thus confirming that the thermal defects on MnO 2 nanorods are due to the presence of oxygen vacancies in the structure [ 81,82 ] . A previous study shows that the intensity of these peaks in the EPR signal is directly proportional to the number of oxygen vacancies [ 83,84 ] . Noticeably the EPR signal shows high intensity for MnO 2 @600°C as compare to MnO 2 and MnO 2 @400°C.…”
Section: Resultsmentioning
confidence: 99%
“…Oxygen vacancies (OV's) that arise from thermal defects are very sensitive to the crystal structure of manganese oxide. OV's in high proportion in a crystalline material can change the geometrical and electronic structure by elongating oxygen bonding (O‐O) for O adsorption, whereas on other hand, the presence of Optimized OV's content can enhance ORR kinetics that has been proved for β‐MnO 2 and λ‐MnO 2 [ 73–89 ] . Figure 6F‐H shows the deconvoluted peaks in high‐resolution spectra of Mn2p for MnO 2 , MnO 2 @400°C and MnO 2 @600°C.…”
Section: Resultsmentioning
confidence: 99%
“…In Fig 2e, the XPS peak in O1s region has been split into two major parts with O ads (531.8 ev) and O latt (530.1 eV) representing surface adsorbed active oxygen and lattice oxygen, respectively. 58,59 The peak intensity of O ads in 7:3 Mn-Ce is higher than pure CeO 2 , indicating the increased concentrations or number of oxygen vacancies. 50,[60][61][62] According to the fitting information in XPS peak software, the concentrations of Ce 3+ in 7:3 Mn-Ce and pure CeO 2 were calculated to be 14.4% and 8.2%, respectively.…”
Section: Morphological and Structural Propertiesmentioning
confidence: 99%
“…Furthermore, the PDOS of 7:3 Mn-Ce oxide revealed that the enhanced peak near the Fermi level originated from Mn-3d.and O-2p, which facilitates the conversion between Ce 3+ and Ce 4+ , making 7:3 Mn-Ce an excellent redox material for supercapacitor applications. 59,67…”
Section: Band Structure and The Density Of Statesmentioning
confidence: 99%